1999
DOI: 10.1034/j.1399-3003.1999.13d35.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of asthma: longitudinal changes in lung function

Abstract: Current knowledge about factors determining outcome of asthma is limited, but observations over the last few decades suggest that active asthma has a negative impact on the longitudinal changes in lung function. This review aims to give an overview of the present knowledge concerning longitudinal changes in lung function, including clinical markers for distinctly poor outcome with regard to lung function, in children and adults suffering from asthma. The majority of patients with asthma have a good prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 114 publications
(171 reference statements)
8
92
1
5
Order By: Relevance
“…But at the end of 6 th month, there was a marked improvement in PFER seen in all the three groups. [9][10][11][12] Initially, the mean FEV1% predicted was 64.1%, 60.1%, and 60.5% for the groups put on ciclesonide, budesonide, and fluticasone, respectively, and the percentage of improvement after bronchodilatation was 20%, 19%, and 21%, respectively, which markedly improved after 6-month treatment and is comparable to the study under taken by Burke et al 1991. 13 Thus, showing significant improvement in the mean values at the end of the treatment, which is comparable to the study by Buhl et al (2006).…”
Section: Discussionsupporting
confidence: 70%
“…But at the end of 6 th month, there was a marked improvement in PFER seen in all the three groups. [9][10][11][12] Initially, the mean FEV1% predicted was 64.1%, 60.1%, and 60.5% for the groups put on ciclesonide, budesonide, and fluticasone, respectively, and the percentage of improvement after bronchodilatation was 20%, 19%, and 21%, respectively, which markedly improved after 6-month treatment and is comparable to the study under taken by Burke et al 1991. 13 Thus, showing significant improvement in the mean values at the end of the treatment, which is comparable to the study by Buhl et al (2006).…”
Section: Discussionsupporting
confidence: 70%
“…individuals with asthma at baseline had quit smoking earlier or had never started smoking due to airway symptoms since no difference between persistent asthma and remission was found among the individuals who ceased smoking during follow up. Previous studies have suggested that smoking may have a negative effect on longitudinal changes in lung function in individuals with asthma [31]. A recent large study on asthma in the general population aged 20–100 years showed that smoking was the main explanation of poor prognosis and comorbidities in individuals with asthma during 4.5 years of follow up [32].…”
Section: Discussionmentioning
confidence: 99%
“…Désirée Larenas-Linnemann, 1 Jorge Salas-Hernández, 2 Juan Carlos Vázquez-García, 3 Ignacio Ortiz-Aldana, 4 Margarita Fernández-Vega, 5 Blanca Estela Del Río-Navarro, 6 María del Carmen Cano-Salas, 7 Jorge Agustín Luna-Pech, 8 José Antonio Ortega-Martell, 9 Jade Romero-Lombard, 10 Erika del Carmen López-Estrada, 11 Jimena Villaverde-Rosas, 12 José Luis Mayorga-Butrón, 13 Mario Humberto Vargas-Becerra, 14 Martín BedollaBarajas, 15 Noel Rodríguez-Pérez, 16 Ambrocio Aguilar-Aranda, 17 Carlos Adrián Jiménez-González, 18 Carlos García-Bolaños, 19 Claudia GarridoGalindo, 20 David Alejandro Mendoza-Hernández, 21 Enrique Mendoza-López, 22 Gerardo López-Pérez, 21 Guillermo Hideo Wakida-Kuzonoki, 23 Héctor Hernán Ruiz-Gutiérrez, 24 Héctor León-Molina, 25 Héctor Martínez-De la Lanza, 26 Héctor Stone-Aguilar, 27 Javier Gómez-Vera, 28 Jorge…”
unclassified